Green Synthesis Nanopartikel Perak Menggunakan Ekstrak Bunga telang (Clitoria ternatea) dan Karakterisasinya - Negara, Satria Putra Jaya; Hasri, Hasri; Kartika, Andi Eka (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Conventional synthesis of silver nanoparticles (AgNPs) generally uses chemical reagents that may pose environmental and health risks, such as generating toxic by-products, causing environmental pollution, and potentially affecting human health. Therefore, the development of eco-friendly synthesis methods using natural materials has become an important research focus. This study aims to synthesize AgNPs using butterfly pea flower (Clitoria ternatea) extract as a natural reducing and stabilizing agent and to evaluate their physicochemical characteristics. The synthesis was carried out through a green synthesis approach by reacting AgNO₃ solution with butterfly pea flower extract at reaction times of 0, 30, 60, 90, and 120 minutes. The formation of AgNPs was monitored using UV–Vis spectrophotometry in the wavelength range of 300–600 nm to observe the Surface Plasmon Resonance (SPR) peak. Functional groups involved in the synthesis process were analyzed using Fourier Transform Infrared (FTIR), while particle size distribution was determined using a Particle Size Analyzer (PSA). The results showed SPR peaks in the range of 380–470 nm, with maximum absorbance at 422 nm after 60 minutes, indicating the optimal synthesis condition. FTIR analysis identified –OH, C–H, C=C, and C–O functional groups derived from secondary metabolites that act as reducing and stabilizing agents. PSA results showed a dominant particle size of approximately 193 nm within the nanometer scale. These findings indicate that butterfly pea flower extract has strong potential as a sustainable and environmentally friendly biomaterial for AgNP synthesis with potential applications in health, environmental, and functional material fields.